Copper(II) Complex Supported on Fe3O4@SiO2 Coated by Polyvinyl Alcohol as Reusable Nanocatalyst in N‐Arylation of Amines and N(H)‐ Heterocycles and Green Synthesis of 1H‐Tetrazoles. Issue 5 (5th February 2018) - Sardarian, Ali Reza; Eslahi, Hassan; Esmaeilpour, Mohsen
Abstract: In this paper, copper(II) based catalyst bearing polyvinyl alcohol immobilized on Fe3 O4 @SiO2 was synthesized and fully characterized by FT‐IR, XRD, TEM, FE‐SEM, DLS, UV‐Vis, XPS, EDX, TGA, VSM, NMR, ICP and elemental analysis techniques. Then, the performance of this magnetic heterogeneous system was investigated in the N ‐arylation of nitrogen heterocycles and alkyl amines with aryl halides to produce the desired coupled products in good to excellent yields without using external ligands or additives as promoters. Also, this reusable copper based magnetic nanocatalyst was employed in one‐pot three component and green synthesis of 5‐substituted 1 H ‐tetrazoles in excellent yields through the click reaction of aliphatic and aromatic aldehydes with hydroxylamine hydrochloride and azide salt. This catalytic system was easily recovered by a magnetic field and reused for at least 7 times without distinct deterioration in catalytic activity. Also, the analysis of the reaction mixture by the ICP technique showed that the leaching of the catalyst was negligible. Abstract : In the best of our knowledge, a novel Cu‐based magnetic and heterogeneous nanocatalyst (Fe3 O4 @SiO2 ‐TCT‐PVA−Cu(II)) was synthesized and investigated in the N ‐arylation of nitrogen heterocycles and alkyl amines with aryl halides. Also, this catalyst was applied in one‐pot three component green synthesis of 5‐substituted 1 H ‐tetrazoles in excellent yields through the click reaction of aliphatic and aromatic aldehydes with hydroxylamine hydrochloride and azide salt.